The interaction between poultry and Triatoma infestans Klug, 1834 (Hemiptera: Reduviidae) in an experimental model. - Schweigmann, N.J. (1995)
This paper compares the predation pressure that ducks and chickens exert on triatomines. For the tests, these birds were placed in individual boxes together with a known number of Triatoma infestans and left to interact from 6 p.m. till the next morning, involving a long lasting period of complete darkness limited by two short-term periods of semi-darkness. There was a shelter which could prevent the bugs from being predated. The number of live and dead triatomines was recorded, considering missing bugs as predated by the birds. Ducks exhibited a greater predatory activity than chickens, that could be due to a long term active period at night while chickens sleep motionless from sunset to dawn. Surviving triatomines that had fed on chickens outnumbered those fed on ducks suggesting that these were less accessible to the triatomine biting. If ducks are better than chickens to detect and eat bugs and to interfere with their feeding in the field, an increase in duck number might help to diminish triatomine density. Further research is needed to determine the feasibility of application of these experimental results.